An autoimmune cause of confusion in a patient with a background of hypothyroidism - Brown, Jonathan (Endocrinol Diabetes Metab Case Rep, 2019)
A 68-year-old previously independent woman presented multiple times to hospital over the course of 3 months with a history of intermittent weakness, vacant episodes, word finding difficulty and reduced cognition. She was initially diagnosed with a TIA, and later with a traumatic subarachnoid haemorrhage following a fall; however, despite resolution of the haemorrhage, symptoms were ongoing and continued to worsen. Confusion screen blood tests showed no cause for the ongoing symptoms. More specialised investigations, such as brain imaging, cerebrospinal fluid analysis, electroencephalogram and serology also gave no clear diagnosis. The patient had a background of hypothyroidism, with plasma thyroid function tests throughout showing normal free thyroxine and a mildly raised thyroid-stimulating hormone (TSH). However plasma anti-thyroid peroxidise (TPO) antibody titres were very high. After discussion with specialists, it was felt she may have a rare and poorly understood condition known as Hashimoto’s encephalopathy (HE). After a trial with steroids, her symptoms dramatically improved and she was able to live independently again, something which would have been impossible at presentation. LEARNING POINTS: In cases of subacute onset confusion where most other diagnoses have already been excluded, testing for anti-thyroid antibodies can identify patients potentially suffering from HE. In these patients, and under the guidance of specialists, a trial of steroids can dramatically improve patient’s symptoms. The majority of patients are euthyroid at the time of presentation, and so normal thyroid function tests should not prevent anti-thyroid antibodies being tested for. Due to high titres of anti-thyroid antibodies being found in a small percentage of the healthy population, HE should be treated as a diagnosis of exclusion, particularly as treatment with steroids may potentially worsen the outcome in other causes of confusion, such as infection.